The characteristics and geographic distribution of robot hubs in U.S. manufacturing establishments - Erik Brynjolfsson; Catherine Buffington; Nathan Goldschlag; J. Frank Li; Javier Miranda; Robert Seamans (Halle Institute for Economic Research (IWH), 2023)
We use data from the Annual Survey of Manufactures to study the characteristics and geography of investments in robots across U.S. manufacturing establishments. We find that robotics adoption and robot intensity (the number of robots per employee) is much more strongly related to establishment size than age. We find that establishments that report having robotics have higher capital expenditures, including higher information technology (IT) capital expenditures. Also, establishments are more likely to have robotics if other establishments in the same Core-Based Statistical Area (CBSA) and industry also report having robotics. The distribution of robots is highly skewed across establishments' locations. Some locations, which we call Robot Hubs, have far more robots than one would expect even after accounting for industry and manufacturing employment. We characterize these Robot Hubs along several industry, demographic, and institutional dimensions. The presence of robot integrators and higher levels of union membership are positively correlated with being a Robot Hub.
Keywords: L64; O34; O36; O4; 330; labor; manufacturing; robot; technology adoption